Comorbidity and «masks» in neurology - Arina L. Lushchik; Irina A. Firsova; Olga A. Panina (LLC "MEDIAFORMAT", 2024)
The purpose of the study is to demonstrate the difficulties faced by a primary care physician at the time of diagnosis in making a diagnosis and the need for medical compliance for the proper management of patients with comorbid pathology. Materials and methods. 3 clinical cases of patients examined from complaints and objective data to laboratory and instrumental examination methods are presented. Analysis of patient outpatient records under observation and treated at the Voronezh City Clinical Polyclinic No. 4. Study of the provided medical documentation, anamnesis data, and conclusions of specialist doctors. The results of ECG, EEG, ultrasound, MRI and RCT of the brain, ENMG, CT of the OGK, and laboratory data were analyzed. Results. The importance of the clinical picture totality in every case, close attention to routine blood tests in the practice of a neurologist, the importance of the data obtained together and separately, close cooperation with related specialists as part of the medical commission is shown. Conclusion. Neurological manifestations of the disease occur in various other pathologies. Therefore, it is very important to take into account all deviations when examining a patient, since sometimes the true diagnosis is masked by other diseases. Only an integrated approach in the examination of patients with complex cases allows us to make a correct diagnosis and conduct adequate therapy.